In Vitro Detoxification of Aflatoxin B(1), Deoxynivalenol, Fumonisins, T-2 Toxin and Zearalenone by Probiotic Bacteria from Genus Lactobacillus and Saccharomyces cerevisiae Yeast - Chlebicz, Agnieszka (Probiotics Antimicrob Proteins, 2019)
The aim of the following research was to determine the detoxification properties of probiotic Lactobacillus sp. bacteria (12 strains) and S. cerevisiae yeast (6 strains) towards mycotoxins, such as aflatoxin B(1), deoxynivalenol, fumonisins, T-2 toxin and zearalenone, which pose as frequent feed contamination. The experiment involved analysing changes in concentration of mycotoxins in PBS solutions, after 6, 12 and 24 h of incubation with monocultures of tested microorganisms, measured by high-performance liquid chromatography (HPLC). We found that all strains detoxified the mycotoxins, with the highest reduction in concentration observed for the fumonisin B(1) and B(2) mixture, ranging between 62 and 77% for bacterial strains and 67–74% for yeast. By contrast, deoxynivalenol was the most resistant mycotoxin: its concentration was reduced by 19–39% by Lactobacillus sp. strains and 22–43% by yeast after 24 h of incubation. High detoxification rates for aflatoxin B(1), T-2 toxin and zearalenone were also observed, with concentration reduced on average by 60%, 61% and 57% by Lactobacillus, respectively, and 65%, 69% and 52% by yeast, respectively. The greatest extent of reduction in the concentration for all mycotoxins was observed after 6 h of incubation; however, a decrease in concentration was noted even after 24 h of incubation. Thus, the tested microorganisms can potentially be used as additives to decrease the concentrations of toxins in animal feed.